Некоторые проблемы словенской фразеографии (к выходу в свет первого фразеологического словаря словенского языка Янеза Кебера) - Коницкая, Елена Михайловна Михайловна (Slavistica Vilnensis, 2012)
В 2011 году в Любляне вышел в свет Slovar slovenskih frazemov — первый одноязычный словенский фразеологический словарь (далее — SSF), составленный Янезом Кебером, известным словенским фразеологом1. Это большое событие в словенской лексикографии, успешно развивающейся с конца ХХ в. во многих областях: в 1970–1991 гг. вышел Словарь словенского литературного языка (далее — SSKJ)2 , в 2001 г. — орфографический словарь [PS] (130000 слов), в 1977–2007 гг. — этимологический словарь Ф. Безлая [FB], а в 1997, 2003, 2009 гг. — этимологический словарь М. Сноя3 [MS]; с 90-х гг. XX в. выходят терминологические словари [Коницкая 1999, 251]; о бурном развитии этой области лексикографии говорит факт, что лишь за 2011 г. вышли словари: ботанический [BTS], фармацевтический [FTS], горнолыжного спорта [SSS]; выходили также диалектные словари4, появился первый том Словенского лингвистического атласа [SLA 2011]....Jelena KonickajaIssues in Slovene Phraseology: The Publication of the First Phraseological Dictionary of Slovene, by Janez KeberSignificant changes are occurring presently in phraseology as an area of linguistics, which are linked to new methods (attention to the concept of language world pattern, culturological and contrastive studies). The article examines several controversial solutions proposed in the first Slovene phraseological dictionary, which was issued in SRC of the Slovene Academy of Sciences in 2011 (Janez Keber, Slovar slovenskih frazemov). The article analyses variativity, synonymy, the establishment of phraseological meaning, and issues of the derivation of phraseologisms (idiom formation), as well as crosslinguistic parallels. The many instances of vagueness and contradictions found in Keber's dictionary point to the need for a deeper interpretation of issues regarding the description of phraseology and the development of a strict theoretical foundation. Moreover, the wide phraseological material in the dictionary and the general reworking of the theory of Sloмene phraseology allows one to hope for the publication of new specialized Slovene phraseological dictionaries.Keywords: Slovene phraseology, phraseological Dictionary, synonymy, idiom formation.